Comparing Surgical Complications of Donors and Recipients in Retroperitoneoscopic versus Mini-Incision Donor Nephrectomy: A Single-Center Experience. (28th January 2013) - Koch, Martina; Bachmann, Alexander; Nashan, Bjoern
Abstract : Anterior vertical mini-incision donor nephrectomy (MIDN) has been used as the standard retrieval procedure in our center. Though the MIDN approach was tolerated very well with low complication rates, there were especially cosmetic reasons, to consider a change of procedure. Hence we switched to a total retroperitoneoscopic donor nephrectomy (RPDN) in 2011. We compared the outcome and surgical complications of donors and recipients of the first 30 RPDNs performed with 30 consecutive MIDN procedures. In both techniques, right and left nephrectomies were carried out. After a very short learning curve, the mean RPDN operation times were shorter compared to the MIDN (109 versus 171 min, P < 0.01 ) and donors were discharged earlier. No major complications occurred in the RPDN group and complications were less frequent compared to MIDN (17% versus 40%). The renal function in the recipients was equivalent in both groups at the time of discharge and after one year. We conclude that RPDN is easy to learn for a surgical team experienced in open retroperitoneal donor nephrectomy. The change of the retrieval technique is safe for the donor and the recipient regarding surgical complications and recipients' renal function. Donors benefit from RPDN due to earlier hospital discharge and faster recovery.